2018
DOI: 10.2217/pgs-2017-0191
|View full text |Cite
|
Sign up to set email alerts
|

Patient Perspectives Following Pharmacogenomics Results Disclosure in an Integrated Health System

Abstract: Participants reported value in both methods of PGx testing. Patient experiences, understanding and result utilization will play an important role in informing future development and implementation of PGx programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 44 publications
3
54
1
Order By: Relevance
“…Consistent with existing literature on patient understanding of PGx test results, this study identified gaps in understanding of PGx test results even among a mostly highly educated study population [2][3][4]14]. Most participants requesting genetic counseling (54%) were seeking general assistance with understanding their PGx result reports, often alluding to uncertainty regarding whether they should or should not take a given medication in the future based on their results.…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…Consistent with existing literature on patient understanding of PGx test results, this study identified gaps in understanding of PGx test results even among a mostly highly educated study population [2][3][4]14]. Most participants requesting genetic counseling (54%) were seeking general assistance with understanding their PGx result reports, often alluding to uncertainty regarding whether they should or should not take a given medication in the future based on their results.…”
Section: Discussionsupporting
confidence: 70%
“…The notion of PGx results potentially leading people to conclude that any and all adverse events from a drug was due to their genetic make-up was noted by Lee et al [16] in their focus group study comparing the attitudes and perceptions of individuals exposed to PGx-guided care versus those of individuals with traditional care. On the other hand, some studies have found that individuals receiving PGx test results may be more medication compliant and willing to tolerate some side effects if PGx testing was utilized to assist with drug and dose selection [2,16,18,19]. Results from a study by Haga et al [14] lend further support to the hypothesis that PGx testing may improve patient adherence to medications.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations